Black ginseng under forest as a natural antidepressant: insights into its active components and mechanisms - Sui, Yixuan; Tan, Yiying; Li, Yajing; Gao, Xiaochen; Lu, Han; Shen, Jiaming; Hu, Xuesheng; Wang, Lei; Zhao, Liting; Sun, Jiaming; Li, Chunnan (Frontiers in Chemistry, 2025)
Depression is a psychological disorder with significant global impact. It is widely hypothesized that this disorder is associated with neuroinflammation, which disrupts neural homeostasis through various pathways. This study aims to investigate the effective compounds and mechanisms of Black Ginseng under forest (BG) in combating neuroinflammation. Utilizing methods such as UPLC-QE Orbitrap-MS, network pharmacology, molecular docking, and cell biology, the efficacy of BG was demonstrated, and its active components were identified. Cell viability and apoptosis were assessed using Trans well migration assays and flow cytometry. The mRNA expression of target genes was confirmed through real-time quantitative PCR (RT-qPCR), elucidating the anti-neuroinflammatory mechanism. The results indicated that BG exhibited a more pronounced effect on ameliorating neuroinflammatory conditions compared to Ginseng under forest (FG). The main active components were found through research and development, including Ginsenoside F1, Ginsenoside Rk1, Ginsenoside Rg3, etc. Among these, Ginsenoside F1 emerged as the most potent active component for treating neuroinflammation, as evidenced by reduced cell migration and apoptosis. The study demonstrates that BG can modulate the PI3K-Akt signaling pathway, leading to a reduction in the expression levels of AKT1, MAPK1, PIK3CA, EGFR, and other mRNAs. These findings suggest that BG is a promising natural antidepressant, providing both theoretical and experimental foundations for the development of new antidepressants based on BG and its active components.